Design and fabrication of solar powered membrane distillation system - Azzura Izzaty, Abu Bakar (2018)
Membrane distillation system is one of the solution to overcome the pollution issues that have been wide spreading. The system also solves the issue in the shortage of clean water supply that were escalating day by day especially in our own country, Malaysia. Membrane Distillation required two form of energy in order to perform its activity that is heat and electrical energy. In order to improve the system, the energy consumption of the system could be lowered by solar power. As solar power are reliable for providing thermal and electrical energy for the system as solar thermal collector and photovoltaic cells. With the solar thermal collector combined with the membrane distillation system, the temperature of the heat needed for the solar collector could be provided without having the auxiliary electric heater accompanied. The performance of the collector were simulated and the best design parameters were identified for the thermal collector so that it could worked at its maximum efficiency. The performance of the solar collector plays an important role in the first step on establishing this project to see whether the combining of solar thermal collector with the membrane distillation system could give the same result as there are no electrical heater included in the system. The mechanism of the solar powered membrane distillation system were reviewed to make sure the system would be able to maintain the temperature of the desired fluid in the feed tank of the system and increase the temperature of the fluid at the same time.